Collaborative roles of music therapists and teachers for students on the autism spectrum: An integrative review. - Ng, Estelle L. E.; Lee, Jin Hyung (Nordic Journal of Music Therapy, 2026)
Introduction: Music therapists and school teachers often collaborate to support the educational and developmental needs of students on the autism spectrum. Clarifying their roles can strengthen teamwork and improve student outcomes. Thus, this integrative review examines their collaborative relationships, exploring the goals, music interventions, and professional titles used for these interventions to inform professional development. Method: A thorough search of five online databases was conducted, complemented by a hand search of major music therapy journals. The selected studies were analyzed based on the integrative review methodology. Results: Twelve publications were identified. Analysis of these studies revealed that music therapists and teachers each performed distinct roles during collaboration, tailored to their areas of expertise. The review also demonstrated that collaborative work targeted a wide range of goal domains and utilized a variety of interventions. Discussion: This review provided insights into the nature of consultations provided by both music therapists and teachers. The review also suggested factors that music therapists should consider when selecting or designing musical materials for teacher-mediated interventions. Implications for further collaborative practice and potential research directions are discussed.